(untitled) (Journal of Medicine, 2019)
Enteric fever continues to be a major global public health problem, predominantly in the developing countries, including Bangladesh. Mortality rates due to enteric fever can be reduced from 30% to <1% by providing effective antimicrobial therapy which is facing challenges due to emerging antimicrobial resistance. The changing trend of antibiotic susceptibility pattern of Enteric fever from pre-antibiotic era through susceptible antibiotics, then multidrug resistance (MDREF) followed by re-emergence of sensitivity to some older resistant antibiotics pose therapeutic challenges for the physicians. The purpose of this review article is to compare the antibiogram of Salmonella isolates of different recent studies and analyzing the changing trend of antibiotic resistance pattern for further successful management. This may also enable planning of antibiotic recycling wherever feasible. J MEDICINE JAN 2020; 21 (1) : 51-54